Implementation of Corporate Social Responsibility (CSR) In Improving The Reputation of Islamic Banking: A Perspective of Shariah Enterprise Theory - Amaliah Liwan, Nadhilah; Haliah, Haliah; Nirwana, Nirwana (Dinasti International Journal of Economics, Finance & Accounting, 2023)
This study underscores the importance of Corporate Social Responsibility (CSR) in the context of Islamic banking, which considers economic, moral, and ethical aspects in accordance with Islamic principles. Despite being the main focus of companies around the world, the concrete impact of CSR implementation in a sharia perspective on corporate reputation still needs to be better understood. This study uses the literature review method, by collecting and analyzing 13 journals from various sources of information related to the form of CSR in Islamic banks in the SET perspective. The results show that Islamic banks that implement CSR based on Shariah Enterprise Theory (SET) can improve their corporate reputation. By complying with the sharia principles in the SET concept, Islamic banks are able to build a positive image in the eyes of customers, investors, and the community, as well as create a favorable environment, and increase stakeholder trust. This study has an important contribution in illustrating the importance of CSR disclosure in the SET perspective to enhance the reputation of Islamic banks and promote sustainability in the Islamic banking industry.